The CATALYTIC tool to assess feasibility of implementing evidence-based interventions for cardiovascular diseases in 46 low- and middle-income countries: survey outcomes and tool reliability testing - Ojo, Temitope; Yassin, Hanan; Sowunmi, Esther; Hameed, Tania; Ryan, Nessa; Gyamfi, Joyce; Shelley, Donna; Ogedegbe, Olugbenga; Peprah, Emmanuel (Frontiers in Public Health, 2025)
BackgroundEvidence-based interventions (EBI) for cardiovascular disease (CVD) in low- and middle-income countries (LMIC) may face feasibility challenges due to the inadequacy of existing instruments. To address this, researchers developed the Contextual Index of Feasibility on Early-Stage Implementation in LMIC (CATALYTIC) tool, which integrates contextual factors into the assessment of feasibility.MethodsThe tool’s items were developed through a systematic review and key informant interviews, and were later assessed for relevance and importance by 13 LMIC researchers and implementers employing a Delphi technique. The survey was then tested for usability by five individuals with CVD experience in LMIC. The CATALYTIC tool consists of 17 items that measure contextual factors that directly influence early-stage LMIC implementation. Descriptive analysis, logistic regression, item reliability using Cronbach’s alpha, and exploratory factor analysis (EFA) were performed on survey data.ResultsIn a survey of 216 respondents from 46 countries, 63.4 to 81.5% of respondents noted a significant impact of contextual factors on implementation feasibility, with high reliability (Cronbach’s alpha 0.88) for 12 items. The majority of interventions focused on patient-level care in rural settings. The survey items align primarily with constructs related to implementation climate and readiness for implementation, as well as inductive themes addressing existing needs and barriers to inform intervention design. The survey found diversity in geographic and experiential backgrounds, with significant representation from South Africa, Mexico, and India. Over a third identified as researchers, and 15% held multiple roles. The survey identified three distinct factors influencing how researchers and implementers assess CVD intervention feasibility in LMIC. A 6% increase in odds for moderately feasible interventions was linked to each point increase in the composite score of perceived contextual influence.ConclusionOverall, the CATALYTIC tool with 12 reliable survey items can help researchers and implementers elucidate perceptions of contextual factors influencing the feasibility of CVD-related EBI in LMIC. The survey items reflect respondents’ practical focus in resource-limited settings and can inform intervention design by addressing existing needs and barriers. The tool’s integration of contextual factors into the assessment of feasibility can help overcome the inadequacy of existing instruments by providing more tailored and conceptually clear assessments of feasibility.